Values of Local Wisdom in the Jenang Tebokan Carnival Tradition in Kaliputu Village Kudus City Central Java - Rindang Viqriani; Yusuf Falaq (JURNAL PENDIDIKAN IPS, 2023)
The aim of this research is to find out what local wisdom values ​​exist in the jenang tebokan carnival tradition in Kaliputu Village, Kudus City, Central Java. This research uses library methods. Namely, the data collected was obtained from various scientific literature (library research). Then what is done in data analysis is by collecting data, then classifying it and drawing conclusions. The results of this research are concluded as follows: (1) Tradition is the concept of beliefs and behavior that are passed down from generation to generation. The concepts aimed at include religion, social customs, cuisine and art. Tradition comes from Latin, namely traditio, meaning "passed on" or what is called custom. (2) Jenang tebokan is jenang in a tray. The term "tebokan" comes from the word tebok which means a tray made of woven bamboo. (3) Local wisdom values in the jenang tebokan tradition, namely religious values, social values ​​and cultural values.